Designing SeW Quartet Card for Primary School Students - Anggi Rizka Pustika; Ima Widyastuti; Saviera Zulykha Ajeng (Universitas Sarjanawiyata Tamansiswa, 2021)
Though Bahasa becomes the second language in Indonesia, some lower class students of primary school face difficulties in compiling sentences into short texts. The present study aims to design a SeW – Sentence Writing quartet card for assisting the Grade 2 students of primary school in making short texts. The SeW quartet card was designed by following the design thinking steps namely empathize, define, ideate, prototype, and test. This was designed by adopting the concept of quartet card game and pictoral card games which the students are familiar with. The study has not been tested to the real students, however, the product has been successfully tested to a younger child as well as the group of Grade 2 teachers in Yogyakarta, Indonesia.Keywords: design thinking, SeW quartet card, short text, Bahasa